2022
DOI: 10.3390/vaccines10020187
|View full text |Cite
|
Sign up to set email alerts
|

Ex Vivo Evaluation of Mucosal Responses to Vaccination with ALVAC and AIDSVAX of Non-Human Primates

Abstract: Non-human primates (NHPs) remain the most relevant challenge model for the evaluation of HIV vaccine candidates; however, discrepancies with clinical trial results have emphasized the need to further refine the NHP model. Furthermore, classical evaluation of vaccine candidates is based on endpoints measured systemically. We assessed the mucosal responses elicited upon vaccination with ALVAC and AIDSVAX using ex vivo Rhesus macaque mucosal tissue explant models. Following booster immunization with ALVAC/AIDSVAX… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 84 publications
(85 reference statements)
0
1
0
Order By: Relevance
“…Furthermore, a multi-site study has shown that protocol standardization provides measurement consistency among different laboratories ( 54 ). This model recapitulates the histological and immunological characteristics of the genital mucosae and early responses to stimuli can be measured ( 55 , 56 ). However, limitations include (i) progressive loss of architecture despite the maintenance of CD4:CD8 T cell ratios and sufficient viability to sustain viral replication for more than 10 days ( 57 ); (ii) paucity of data regarding preservation of immune competence ( 58 ); (iii) limitation to demonstrate sterilizing protection.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a multi-site study has shown that protocol standardization provides measurement consistency among different laboratories ( 54 ). This model recapitulates the histological and immunological characteristics of the genital mucosae and early responses to stimuli can be measured ( 55 , 56 ). However, limitations include (i) progressive loss of architecture despite the maintenance of CD4:CD8 T cell ratios and sufficient viability to sustain viral replication for more than 10 days ( 57 ); (ii) paucity of data regarding preservation of immune competence ( 58 ); (iii) limitation to demonstrate sterilizing protection.…”
Section: Discussionmentioning
confidence: 99%